2012
DOI: 10.2174/1876396001205010146
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Nutrients and Noncommunicable Diseases

Abstract: There is a marked increase in our knowledge about the role of the nutritional factors in the global dimensions of the noncommunicable diseases (NCDs). Recent studies indicate that there is coexistence of nutritional deficiencies and appreciable over-nutrition in conjunction with physical inactivity, due to urbanization and industrialization. Dietary factors may predispose inflammatory dysfunctions in tissues predisposing to central obesity and overweight that are risk factors of NCDs. Mortality and burden of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 58 publications
4
13
0
1
Order By: Relevance
“…Millions of deaths occur every year due to a lack of health education and poor health public policies because people and populations living with scant resources, have no opportunity for health education due to poor public health services [16][17][18]. These findings further confirm the old hypothesis that emergence of NCDs may have a sequence during transition from under-nutrition and poverty to affluence; (Fig.…”
Section: Chronic Lung Disease S E S -1 -3 S E S -4 -5 T O T a L S E Ssupporting
confidence: 67%
See 2 more Smart Citations
“…Millions of deaths occur every year due to a lack of health education and poor health public policies because people and populations living with scant resources, have no opportunity for health education due to poor public health services [16][17][18]. These findings further confirm the old hypothesis that emergence of NCDs may have a sequence during transition from under-nutrition and poverty to affluence; (Fig.…”
Section: Chronic Lung Disease S E S -1 -3 S E S -4 -5 T O T a L S E Ssupporting
confidence: 67%
“…In a more recent study among 7519 subjects with self-reported CAD or stroke event from countries with varying income levels, the prevalence of healthy lifestyle behaviours was low, with even lower levels in poorer countries [16]. However, this study did not report on attributes of social class; education, housing, occupation, consumer durables and household income which appear to be important determinants of health behaviours [17][18][19][20]. One recent study showed that the intake of prudent foods was significantly lower and that of Western foods, significantly higher among patients with NCDs compared to decedents who died due to injury and accidents [21] ( Table 1).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The major cause of death in high-income countries is noncommunicable disease [24]. The dominant risk factor for death due to noncommunicable diseases is diet [1]. Thus, careful control and monitoring of the diet in the kindergarten stage may help to control food palatability in adults and may decrease the likelihood of developing a noncommunicable disease.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a marked increase in our knowledge of the role of diet selection in the global dimensions of noncommunicable diseases [1]. The principal risk factors for noncommunicable diseases vary widely depending on the country.…”
Section: Introductionmentioning
confidence: 99%